EFISIENSI PEMASARAN JERUK DI DESA BANUA, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Heribertus Arut; I Made Budiasa; Putu Eka Pasmidi Ariati (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
The research objective was titled the efficiency of citrus marketing in Banua Village, Kintamani District, Bangli Regency, is tu analyze 1. Marketing costs, marketing margins, farmer share. 2. The level of efficiency of the marketing channel. The analitycal method used is marketing margin analysis, farmer share analysis and efficiency analysis. This research was conducted from December to February 2021. Responden in the study were 45 farmers using the simple random sampling method and 15 people at the marketing institute consisted of 3 collectors 5 retailers and 7 consumers, using in the snowball sampling method. Based on the research results on the analysis of marketing costs, marketing margins, and marketing efficiency of siam oranges. The following conclusions are obtained: 1. At level I marketing channels, there is not costs and marketing margin (Rp. 0), farmer share 100%, marketing efficiency 0,00%. 2. In the second level marketing channel, the marketing cost is Rp. 2.500, marketing margin of Rp. 3.000, farmer share 57%, marketing efficiency 35,71%. 3. At level III marketing channels, the marketing costs are Rp. 4.500, marketing margin of Rp. 6.000, farmer share 40%, marketing efficiency 45.00%. 4.The most efficient marketing channels is the level 1 channel (products sold directly from farmers to consumers).